If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3d = 9 + 6d Solving 3d = 9 + 6d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-6d' to each side of the equation. 3d + -6d = 9 + 6d + -6d Combine like terms: 3d + -6d = -3d -3d = 9 + 6d + -6d Combine like terms: 6d + -6d = 0 -3d = 9 + 0 -3d = 9 Divide each side by '-3'. d = -3 Simplifying d = -3
| 3ab-2-4ab= | | 20k^2-38+12=0 | | 5x+13-8x=17-17x+14x-4 | | 5m+1=10+4m | | -9+4r=1+2r | | -1(4n+2)=-2(2n-1) | | 11x-89=7x+19 | | 200m-5600=0 | | 5x+30=3x-10 | | 0=5x^2-12x+4 | | -3f=-f+6 | | 5(3r-1)=55 | | 8n-2n+7=29 | | 4n^2+21n-18= | | 3n+2=-19 | | 10x-1=4x+23 | | 2.5x=x+100*2.5 | | 0.5m=10 | | 324+x^2=900 | | 9v=-10+8v | | z=xl | | 4(x^2)-32=84 | | 2.5x=x+100 | | 6-4n+3n=20-25 | | -7(4x+3)=-21 | | 9+3+2a-2=a+4 | | x^2-32=21 | | 8x-55=5x-7 | | 2(w-58)=(w+497)-58 | | 8c+d=12d-5 | | 18+13+n=-9 | | 4x^2+3x+8=8x+7 |